2014
DOI: 10.1016/j.neuroscience.2014.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Localization of excitatory amino acid transporters EAAT1 and EAAT2 in human postmortem cortex: A light and electron microscopic study

Abstract: The process of glutamate release, activity, and reuptake involves the astrocyte, the presynaptic and postsynaptic neuron. Glutamate is released into the synapse and may occupy and activate receptors on both neurons and astrocytes. Glutamate is rapidly removed from the synapse by a family of plasma membrane excitatory amino acid transporters (EAATs), also localized to neurons and astrocytes. The purpose of the present study was to examine EAAT labeling in postmortem human cortex at the light and electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 119 publications
(146 reference statements)
3
75
2
1
Order By: Relevance
“…Furthermore, they detected EAAT1 protein in neurons, where it was present in the soma, all parts of the axon, dendritic spines and in the postsynaptic density (PSD). This is at variance with most of the other studies which have located EAAT1 in astrocytes; the presence of an apparent EAAT1 antigen in neurons might have been caused by changes taking place in the tissue during the post-mortem delay [17,18] but there are other ways to explain the observed discrepancies, including the occurrence of splice variants. EAAT1 is now known to be subject to alternate splicing and to give rise to multiple variant proteins.…”
Section: Location Of Eaats and Their Possible Roles In Brain Functionscontrasting
confidence: 77%
See 2 more Smart Citations
“…Furthermore, they detected EAAT1 protein in neurons, where it was present in the soma, all parts of the axon, dendritic spines and in the postsynaptic density (PSD). This is at variance with most of the other studies which have located EAAT1 in astrocytes; the presence of an apparent EAAT1 antigen in neurons might have been caused by changes taking place in the tissue during the post-mortem delay [17,18] but there are other ways to explain the observed discrepancies, including the occurrence of splice variants. EAAT1 is now known to be subject to alternate splicing and to give rise to multiple variant proteins.…”
Section: Location Of Eaats and Their Possible Roles In Brain Functionscontrasting
confidence: 77%
“…There are intriguing exceptions in the literature, though. For example, Roberts et al [17] reported that EAAT1 labelling in human brain was located on the plasma membrane of astrocytes but also in the soma and nucleus. Furthermore, they detected EAAT1 protein in neurons, where it was present in the soma, all parts of the axon, dendritic spines and in the postsynaptic density (PSD).…”
Section: Location Of Eaats and Their Possible Roles In Brain Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to published electron microscopic studies, SLC1A2 is mainly present in astrocytic soma and processes surrounding capillaries and axon terminals mainly around glutamatergic synapses, consistent with its role in facilitating glutamate reuptake and limiting glutamate spillover (Roberts et al, 2014). SLC6A1…”
Section: Chronic Cerebral Hypoperfusion Effects On Gabaergic / Glutammentioning
confidence: 70%
“…A study on rat capillaries revealed little or no EAAT staining on the abluminal surface of brain capillaries (7). However, a recent electron microscopy study by Roberts et al showed a clear EAAT-1 expression in brain capillary endothelial cells from human postmortem cortex samples (17).…”
Section: Expression In Intact Brain Capillariesmentioning
confidence: 99%